Tud-1 supported vanadium-doped titania photocatalyst - Chik, Yong Wi (2015)
New photocatalyst of Techniche Universiteit Delft-1 (TUD-1) supported 5 mol% V doped TiO2 (5V-TiO2 /TUD-1) exhibited enhanced activity in methylene blue photodegradation. XRD results revealed the presence of both anatase and rutile phases in the V-doped TiO2 sample. After loading onto TUD-1, the crystallinity of the sample dropped significantly, implying well dispersion of both V and TiO2 on the TUD-1. DRUV-Vis results suggested alteration of Ti species in the presence of TUD-1. Besides, the band gap energy of V-doped TiO2 decreased after loading onto TUD-1. The sample 5V-TiO2 /TUD-1 possessed high surface area of 626 m2 /g. The photocatalytic performance of the sample was evaluated through the photodegradation of methylene blue under UV irradiation. It has been demonstrated that 5V-TiO2 /TUD-1 was a better photocatalyst compared to TUD-1 and unsupported V-doped TiO2 . The current findings strongly indicated that TUD-1 played an important role as support to improve the photocatalytic activity of V-doped TiO2.